Design semi-active suspension using magneto-rheological damper - Muhamad Amzansani, Abd Wahab (2010)
This thesis focused on the development of semi- active suspension by using magneto-rheological damper. The MR damper is a type of damper that used MR fluid as working fluid which enables us to change damping force and setting of suspension without need to setting manually damper itself. It can be achieve by changing the current flow on it magnetic circuit.This thesis first introduces MR technology through a discussion of MR fluid and then by giving a broad overview of MR devices that is being developed. After giving the reader an understanding of MR technology and devices, MR damper basics are presented. This section includes a discussion of MR damper types, mathematical fundamentals, and an approach to magnetic circuit design. With the necessary background information covered, MR dampers for automotive use are then discussed. Then come to design part. By using specification same as Proton Waja passive damper, the model was develop by using SOLIDWORK software. The design used twin tube damper with same size of outer tube of OEM damper. The parameter like number of turn, length and diameter of the wire, current induced, magnetic field generated, head piston velocity, and force produced by MR damper was be calculated and discussed. The result show the damper produced 6475.441 Newton of maximum force when 3 ampere of current being applied to the damper. The force generated by damper at 0.5, 1, 1.5, 2, 2.5 and 3 ampere was plotted in a single graph versus piston head velocity in order to give better view of result.